Language and Social Justice in Practice
1 online resource (268 pages)
Keywords: From bilingual education and racial epithets to gendered pronouns and immigration discourses, language is a central concern in contemporary conversations and controversies surrounding social inequality. Developed as a collaborative effort by members of the American Anthropological Association’s Language and Social Justice Task Force, this innovative volume synthesizes scholarly insights on the relationship between patterns of communication and the creation of more just societies. Using case studies by leading and emergent scholars and practitioners written especially for undergraduate audiences, the book is ideal for introductory courses on social justice in linguistics and anthropology.